Computation Technique to Estimate Recombination Value, With an Example Loci of MDH, Esterase and Hypocotyl Colour of Setaria italica - Muhammad Jusuf (Forum Pasca Sarjana, 1989)
Coefficient of recombination between two loci can be estimated from it's maximum likelihood function. Newton approximation method that was combined with computer programation can be used on that estimation. Application of this method to data of Setaria italica F2 population, showed recombination coefficient between Est-3 and MDH-I loci is 33.25 + 2.92% and between hypocotyl color and EST-2 loci is 10.21 + 3.25%.